2019
DOI: 10.1021/acssuschemeng.9b05986
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of ZrB2 in a Si–Cu Melt and Its Potential Application for Refining Si and Recycling Si Waste

Abstract: Based on (i) the low liquidus temperature of Si–Cu systems, (ii) low solubility of Cu in solid Si, and (iii) a strong affinity of Zr to B for the enhanced boride formation, a novel method to remove B from Si using Zr as a trapping agent via a Si–Cu solvent was developed in this study. B-bearing polygonal ZrB x precipitations found at the bottom of test samples were confirmed as ZrB2 by electron probe microanalysis. Thermodynamic analysis revealed that the solubility products of ZrB2 in a Si–Cu melt were 2.50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Furthermore, the zirconium (Zr) additive has been verified by Lei as a more effective one in enhancing B-removal efficiency than the Ti additive in Si–Al melts. In our previous research, intermediate ZrB 2 compounds were found near the bottom part of the Si–Cu alloy sample, which provided direct evidence that B in the Si–Cu melt can be reduced by forming a ZrB 2 precipitate through Zr addition . In addition, the constants of the solubility product were determined to be 4.11 × 10 –12 (1345 K, Si-50.0 atom % Cu) and 2.55 × 10 –12 (1258 K, Si-57.0 atom % Cu), which are lower than the values in Si–Al melts at the same temperature measured by Lei .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the zirconium (Zr) additive has been verified by Lei as a more effective one in enhancing B-removal efficiency than the Ti additive in Si–Al melts. In our previous research, intermediate ZrB 2 compounds were found near the bottom part of the Si–Cu alloy sample, which provided direct evidence that B in the Si–Cu melt can be reduced by forming a ZrB 2 precipitate through Zr addition . In addition, the constants of the solubility product were determined to be 4.11 × 10 –12 (1345 K, Si-50.0 atom % Cu) and 2.55 × 10 –12 (1258 K, Si-57.0 atom % Cu), which are lower than the values in Si–Al melts at the same temperature measured by Lei .…”
Section: Introductionmentioning
confidence: 84%
“…A total of 20 g of solar-grade lump Si (99.9999%) and Cu powder (99.9%) with different quantities of Si-1 mass % B and Si-1 mass % Zr alloys (the same premelted raw materials as introduced in previous papers , ) were put into dense graphite crucibles with high purity (A-type: 30 mm outer diameter (OD), 24 mm inner diameter (ID), 50 mm length; B-type: 20 mm outer diameter (OD), 14 mm inner diameter (ID), 70 mm length) to prepare the Si–Cu alloys with different target quantities of B and Zr. Then, the crucibles were placed into the alumina reaction tube of the SiC resistance furnace.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Even though it has been theoretically and experimentally confirmed that P tends to segregate along Si grain boundaries, its segregation coefficient ( k p = 0.35) is still relatively high compared to metallic impurities, which is usually less than 10 –3 . To further improve the extraction efficiency of P and other impurities, considerable attention has been paid to redistribute impurities by adding alloying elements as impurity getters such as calcium (Ca), magnesium (Mg), titanium (Ti), aluminum (Al), copper (Cu), tin (Sn), , iron (Fe), and nickel (Ni) . The widely known solvent refining usually involves alloying by Al, Sn, Cu, and Fe with a large amount of metal addition (around or more than 50 wt %).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2019, several methods have been presented for the purification and recovery of silicon from DWSSP. It is evident that this topic has become a research hotspot and has garnered significant interest from researchers . The authors’ previous studies have investigated the kinetic mechanism of Al removal via HCl leaching, the dissolution and mineralization behavior of metal elements, and the Si core–SiO 2 shell structure .…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that this topic has become a research hotspot and has garnered significant interest from researchers. 20 The authors' previous studies have investigated the kinetic mechanism of Al removal via HCl leaching, 21 the dissolution and mineralization behavior of metal elements, 22 and the Si core−SiO 2 shell structure. 23 Moreover, the kinetic mechanism of iron removal with H 2 SO 4 leaching, 24 multicomponent acid purification, 25 the combined process of slag treatment and acid leaching, 26 and acid leaching followed by induction furnace melting 27 have also been investigated by other research groups.…”
Section: ■ Introductionmentioning
confidence: 99%